Venous congestion and pulmonary vascular function in Fontan circulation: Implications for prognosis and treatment. (15th November 2018) - Egbe, Alexander C.; Reddy, Yogesh N.V.; Khan, Arooj R.; Al-Otaibi, Mohamad; Akintoye, Emmanuel; Obokata, Masaru; Borlaug, Barry A.
Abstract: Background: Elevation in central venous pressure (CVP) plays a fundamental pathophysiologic role in Fontan circulation. Because there is no sub-pulmonary ventricle in this system, CVP also provides the driving force for pulmonary blood flow. We hypothesized that this would make Fontan patients more susceptible to even low-level elevation in pulmonary vascular resistance index (PVRI), resulting in greater systemic venous congestion and adverse outcomes. Methods: Adult Fontan patients and controls without congenital heart disease undergoing clinical evaluation that included cardiac catheterization and echocardiography were examined retrospectively. Outcomes including all-cause mortality and the development of Fontan associated diseases (FAD, defined as protein losing enteropathy, cirrhosis, heart failure hospitalization, arrhythmia, or thromboembolism) were assessed from longitudinal assessment. Results: As compared to controls ( n  = 82), Fontan patients ( n  = 164) were younger (36 vs 45 years, p  < 0.001), more likely to be on anticoagulation or antiplatelet therapy, and more likely to have atrial arrhythmia or cirrhosis. There was a strong correlation between CVP and PVRI in the Fontan group ( r  = 0.79, p  < 0.001), but there was no such relationship in controls. Elevated PVRI identified patients at increased risk for FAD (HR 1.92, 95% CI 1.39–2.41, p  = 0.01), and composite endpoint of FAD and/or death (HR 1.89, 95% CI 1.32–2.53, p = 0.01) per 1 WU∗m 2 increment. Conclusions: Systemic venous congestion, which is the primary factor in the pathogenesis of FAD and death, is related to even low-level abnormalities in pulmonary vascular function. Multicenter studies are needed to determine whether interventions targeting pulmonary vascular structure and function can improve outcomes in the Fontan population. Highlights: Pulmonary vascular resistance is the primary determinant of systemic venous congestion. Systemic venous congestion is the primary factor in the pathogenesis of Fontan associated diseases (FAD) and death. Therapy targeted a pulmonary vascular resistance may modify risk of FAD and death.